Control of a Telerobotic System Using Wi-Fi and Kinect Sensor for Disabled People with an Industrial Process - Urrea-Onate, E (Institute of Electrical and Electronics Engineers Inc., 2020)
This paper describes the design, implementation and evaluation of a telerobotic system for manipulating a 4DoF robot in real time using the Kinect sensor. The Kinect sensor captures hand gestures and transmits them via Wi-Fi, using an ESP8266 module, to an Arduino Mega board that control two rotational joint and two linear joint. Among the results, the behavior of the system is evaluated by comparing it with one that uses Bluetooth. The objective of this work is to permit to incorporate people with disabilities into the workplace in the control of industrial processes. The results and validation of the system were performed with a group of people who manipulated the robot using hand gestures that performed a manual and automatic process. © 2020 IEEE.